KEKALAHAN PETAHANA PADA PEMILIHAN UMUM 2019: STUDI KASUS CALON LEGISLATIF PARTAI KEBANGKITAN BANGSA - Dewanti, Mike; Al-Hamdi, Ridho; Efendi, David (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2022)
This article examines the factors that led to Agus Sulistiyono's defeat in the 2019 Legislative Elections in the DIY electoral district. These factors are seen with three-dimensional indicators of the power cube theory: visible power, hidden power, and invisible power. Methodologically, this article is the result of qualitative research with a case study approach. In data collection, the results of interviews are the main source to determine the factors that influence the defeat of candidates. This finding shows that there are three indicators. First, visible power which includes the campaign strategy carried out by Agus Sulistiyono using the party constitution route spreads throughout Yogyakarta and synergizes with DPRD candidates from the same party. Second, on the hidden power indicator, by obtaining support from the supporting political parties, as well as money politics practices. Third, there is support from religious leaders. Of the three indicators, visible and hidden power is the most dominant indicator that led to the defeat of Agus Sulistiyono in the 2019 Legislative Election in the DIY Electoral District.